Reliability and repeatability of a modified thoracolumbar spine injury classification scoring system - Lu, Wen-jie; Zhang, Jiaming; Deng, Yuan-guo; Jiang, Wei-yu (Frontiers in Surgery, 2023)
Background: To assess the consistency of the modified system based on the Thoracolumbar Injury Classification and Severity Score (TLICS), as well as to investigate the factors influencing the modified system's consistency. Methods: Five spinal surgeons were chosen at random. The clinical data of 120 patients with thoracolumbar fractures admitted to the Department of Spine Surgery, Ningbo Sixth Hospital from December 2019 to June 2021 were categorized using the modified TLICS system. The data were categorized and graded six weeks later. Using unweighted Cohen's kappa coefficients, the consistency of the modified TLICS system was assessed in five aspects: neurofunctional status, disc injury status, fracture morphology, posterior ligament complex (PLC) integrity, and treatment plan. Results: In terms of reliability, the average kappa values for the subclasses of the modified TLICS system (neurofunctional status and disc injury status) were 0.920 and 0.815, respectively, reaching the category of complete confidence. Fracture morphology and treatment plan had average kappa values of 0.670 and 0.660, respectively, which were basically reliable. The average kappa value of PLC integrity was 0.453, which belonged to the category of moderate confidence. In terms of repeatability, the kappa values of neurofunctional status and disc injury status were highly consistent, with kappa values of 0.936 and 0.879, respectively, indicating perfect confidence. The kappa values for fracture morphology and treatment plan were 0.772 and 0.749, respectively, indicating a level of confidence that meets the basic confidence category. The kappa value of the PLC integrity was 0.561, indicating moderate confidence. Conclusion: Concerning the evaluation of thoracolumbar fracture injuries, the modified TLICS scoring system is user-friendly, simple to master, more exhaustive, accurate, and reliable, with excellent repeatability. The evaluation of neurofunctional status and disc injury status demonstrates a high degree of reliability and repeatability. The consistency of fracture morphology is slightly poor, which is basically credible. The consistency of PLC integrity is poor, and it only has a moderate level of reliability. This may be due to the subjectivity of PLC clinical assessment.